TJ-17 (Goreisan) mitigates renal fibrosis in a mouse model of folic acid-induced chronic kidney disease - Aoi Suenaga; Yasuyuki Seto; Masafumi Funamoto; Masaki Imanishi; Koichiro Tsuchiya; Yasumasa Ikeda (Elsevier, 2023)
Background and purpose: TJ-17 (Goreisan), a traditional Japanese Kampo medicine, has been generally used to treat edema, such as heart failure, due to its diuretic effect. In the present study, we investigate the effects of TJ-17 on chronic kidney disease (CKD). Methods: We the preventive action of TJ-17 against acute kidney injury (AKI) transition to CKD in vivo using a folic acid (FA)-induced mouse model. Mice were treated with food containing TJ-17 at 48 h after FA intraperitoneal injection (AKI phase). Results: Histological analysis, as well as renal function and renal injury markers, deteriorated in mice with FA-induced CKD and were ameliorated by TJ-17 treatment. Increased levels of inflammatory cytokines and macrophage infiltration were also alleviated in mice treated with TJ-17. Renal fibrosis, a crucial factor in CKD, was induced by FA administration and inhibited by TJ-17 treatment. Pretreatment with TJ-17 did not exert an inhibitory effect on FA-induced AKI. The increase in urinary volume in FA-induced CKD mice was ameliorated by TJ-17 treatment, with a concurrent correction of reduced aquaporins expression in the kidney. Conclusion: TJ-17 may have a novel preventive effect against inflammation, oxidative stress, and fibrosis, contributing to innovation in the treatment of CKD.